China's rare earths dominance and policy responses - Philip Andrews-Speed; Anders Hove (The Oxford Institute for Energy Studies, 2023)
Rare earth elements (REEs) have many uses in the energy and defence industries, among others, and demand for them is set to increase rapidly in support of the low-carbon energy transition. Although the REEs are not geologically rare, China dominates the supply chain, accounting for 70% of global rare earth ore extraction and 90% of rare earth ore processing. Notably, China is the only large-scale producer of heavy rare earth ores. This dominance has been achieved through decades of state investment, export controls, cheap labour and low environmental standards. In light of the growing demand for REEs, industrialised countries have started to develop strategies to reduce REE supply chain risks. Measures include promoting the opening of new mines and processing plants - including in third countries - technology measures to reduce demand for REEs, recycling, and international collaboration. Whilst these steps are likely to yield benefits in the long-term, the lead times for most of these initiatives will prevent China's dominance of REE supply chains being significantly diminished before 2030.
Keywords: 330; China; electric vehicles; energy security; Energy Transition; rare earth elements; wind turbines